EXPLORATION OF CONOTOXIN PEPTIDE IN SEA SNAIL (CONUS SP.) SANGIHE ISLANDS AS POTENTIAL ALTERNATIVE ANALGESIC COMPOUNDS - Kurniasih Indrawan, Nilamsari
Conus sp. is a marine predatory animal belonging to the Gastropoda class. Conus sp. has the ability to anaesthetize its prey from the poison it produces. The poison produced by Conus sp. is called Conotoxin. Conotoxin is classified as a small peptide of about 12-30 amino acids with disulfide bonds and mostly targets receptors and ion channels (protein channels) in nerve and muscle tissue. Therefore, Conotoxin is believed to have some potential as a neurodegenerative and analgesic drug. Analgesics are anti-pain medications given to patients to reduce pain. The mechanism of action of analgesics involves the Volted Gated Calcium Channel (VGCC) N-Type (CaV) 2.2 protein, which plays an important role in neurotransmitter release and the regulation of pain. Conotoxin peptides have high variation, so these peptides are difficult to identify, and we still need to know their mechanism and function. One analgesic drug, Ziconotide, is known as a peptide derivative derived from Conus magus. However, Ziconotide still has many weaknesses. Therefore, the purpose of this study is to explore the potential of Conotoxin as an alternative analgesic through docking analysis of Conotoxin peptide with VGCC N-Type CaV 2.2 and isolating the Conotoxin gene using degenerate primers to obtain the nucleotide base sequence of the gene. In this study, a kinship analysis of Conus sp. with Ziconotide-producing Conus magus was carried out. Conotoxin amino acid sequences from species with the closest kinship were collected and continued at the peptide modelling stage using I-TASSER (Iterative Threading ASSEmbly Refinement) Software on the page (https://zhanggroup.org/I-TASSER/). The amino acid sequence of Conotoxin was obtained from Conoserver Webserver (https://www.conoserver.org/). Docking analysis of Conotoxin peptide with VGCC N-Type CaV 2.2 protein using HADDOCK 2.4 software (https://wenmr.science.uu.nl/haddock2.4/). Based on the results of molecular docking and kinship analysis, these species were used as a reference for the design of degenerate primers for the Conotoxin gene and continued PCR with optimization: primer annealing temperature, denaturation temperature, primer concentration and elongation time. The PCR product band was inserted into the pGEMT Easy plasmid vector, and the nucleotide base sequence was determined. The docking results obtained HADDOCK score value of: 1. -62.1 +/- 9.7 (Ac6_5_precursor) from Conus achatinus; 2. -105.6 +/- 9.2 (CnIB) from Conus consors; 3. -86.6 +/- 19.1 (Mi020_2) from Conus miles, 4. 76.1 +/- 7.5 from Conus monachus, 5. -120.9 +/- 4.4 from Conus distans and 5. 61.0 +/- 0.9 from Conus vexillum. The docking results were compared with the HADDOCK score value of redocking VGCC N-Type CaV 2.2 with Ziconotide, which was -64.1 +/- 9.7. Conus specimens were taken from Sangihe islands, and as many as three samples were taken (C1, C2, and C3). The genome of the venom duct organ has been successfully extracted. Identification results using the marker gene Cytochrome c oxidase I (COI) obtained that Conus sp. specimen 1 (C1) has the closest kinship with Conus vexillum. Specimen 2 (C2) and specimen 3 (C3) have the closest kinship with Conus distans. The amplification results of the Conotoxin gene using degenerate primers contained many bands with a DNA size range of 75 700 bp. One PCR product band on specimen C1 is 389bp in size. Three PCR product bands ranging from 300-700bp were isolated from specimen C2, and one PCR product band of 75bp from specimen C3. Samples of C1 and C2 gene isolation results show that the nucleotide base sequence belongs to an unidentified protein coding gene. Based on the results of the research by docking analysis of Conotoxin peptide with VGCC CaV 2.2 protein from other species, it has the potential as an alternative analgesic drug that is better than Ziconotide, and the degenerate primers that have been designed successfully amplify protein-coding genes from the genomes of C1 and C2 samples that have not been identified.